Образний потенціал паремій із компонентом око в «Галицько-руських народних приповідках» - Мацьків, Петро; Matskiv, Petro (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто паремії із соматичним компонентом око в «Галицько- руських народних приповідках». Досліджено семантичні, структурні та емоційно-оцінні особливості цих паремій. Визначено специфіку їхньої тематико-ідеографічної організації, з’ясувано роль аналізованих одиниць у фор- муванні української мовної картини світу та розкрито їхній прагматичний потенціал, смислову структуру.The article focuses on the proverbs with the component of the eye in «Galician-Ruthenian Folk Bywords». Semantic, structural and emotionally-evaluative features of these proverbs have been examined. The systemic relation within the analyzed phraseological series has been traced with the construction of the hierarchical structure of ideographical description of the object under investigation; the role of the culturological information put in the internal form of phraseological units in the process of forming phraseological meaning has been defined. The peculiarities of thematic and ideographic organization of proverbs with somatic component of the eye have been identified (proverbs pointing at moral aspects, traits of character, physiological human needs have been singled out), the role of these units in the formation of the Ukrainian linguistic map of the world has been outlined.
The image-bearing potential of proverbs with the component of the eye in «Galician-Ruthenian Folk Bywords»
Keywords: фразеологізм; компонент око; семантика; соматизм; народна традиція; phraseologism; the component of the eye; semantics; somatism; folk tradition